Dose-dependent anti-inflammatory effect of ketamine in liver ischemia-reperfusion injury - Gundogdu, Zafer; Demirel, Ismail; Bayar, Mustafa Kemal; Ozkan, Zeynep; Bayindir, Serpil; Kocyigit, Fatma; Kahraman, Mustafa (American University of Beirut, 2016)
Introduction: Hepatic ischemia-reperfusion (I/R) injury is commonly observed in severe sepsis, hemorrhagic shock, liver transplantation, hepatic resection, and major trauma. Ketamine suppresses the production of cytokines, such as IL-6 and TNF-?, via NF-?B inhibition. We investigated the anti-inflammatory effects of ketamine in liver I/R injury. Materials and Methods: Female Wistar-Albino rats (n = 18), weighing 150-200g, were divided into three groups (n = 6 each). Group I underwent reperfusion for 4h following 30min of ischemia. Group II received 2.5 mg/kg ketamine IM following 30 min of ischemia and 4h of reperfusion and Group III received 10 mg/kg ketamine IM following 30 of ischemia and 4h of reperfusion. Blood samples were obtained before and after ischemia and reperfusion. MDA, AST, ALT, TNF-?, IL-1?, IL-6, and NO levels were determined. Liver tissue samples were evaluated histologically. Results: Increased TNF-?, IL-1?, and IL-6 levels were observed in all groups post-ischemia versus pre-ischemia (p <0.05). The TNF-?, IL-1?, and IL-6 levels in Group III increased less than they did in Groups I and II (p <0.05). Higher MDA, NO, AST, and ALT levels were found during the ischemia and reperfusion periods compared with during the pre-ischemia period in all groups (p <0.05). The MDA, NO, AST, and ALT levels of rats that received ketamine increased less than did those of Group I (p <0.05). Significantly less injury was observed in the histopathological analysis of livers of rats administered ketamine (p <0.05). Conclusions: Ketamine showed a dose-dependent anti-inflammatory effect in I/R injury in the liver when administered after ischemia. © 2016, American University of Beirut. All rights reserved.
Keywords: IL-1?; IL-6; Ischemia-reperfusion injury; Ketamine; Liver; TNF-?